EVALUATION OF THE IMPACT OF THE DIRECT CASH ASSISTANCE (BLT) PROGRAM IN BONE SUB-DISTRICT, PANGKEP DISTRICT - A.Pananrangi. M; A.M.Ishak Ismail (Sean Institute, 2023)
This study aims to determine the impact evaluation of the Direct Cash Assistance (BLT) program and to determine the factors that impede the evaluation of the impact of the Direct Cash Assistance (BLT) Program in Bone Village, Segeri District, Pangkep Regency. This type of research uses a qualitative research type, data collection techniques namely observation, interviews and documentation. Data analysis techniques, namely data collection, data reduction, data presentation and conclusion. The results of this study indicate that the evaluation of the impact of the Direct Cash Assistance (BLT) program has a positive impact on society, and the factors that influence the evaluation of the impact of the Direct Cash Assistance (BLT) program are implementing skills and coordination between program implementers.